Space Architecture Education for Engineers and Architects Designing and Planning Beyond Earth - Häuplik-Meusburger, Sandra; Bannova, Olga.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book considers two key educational tools for future generations of professionals with a space architecture background in the 21st century: (1) introducing the discipline of space architecture into the space system engineering curricula; and (2) developing space architecture as a distinct, complete training curriculum. Professionals educated this way will help shift focus from solely engineering-driven transportation systems and "sortie" missions towards permanent off-world human presence. The architectural training teaches young professionals to operate at all scales from the "overall picture" down to the smallest details, to provide directive intention-not just analysis-to design opportunities, to address the relationship between human behavior and the built environment, and to interact with many diverse fields and disciplines throughout the project lifecycle. This book will benefit individuals and organizations responsible for planning transportation and habitat systems in space, while also providing detailed information on work and design processes for architects and engineers.
Introduction: Space Architecture as a Discipline -- Building and Planning -- Different Educational Systems and Approaches -- Case Studies and examples -- Conclusions -- Appendices.
Keywords: Aerospace engineering; Astronautics; Interior architecture; Solar system; Aerospace Technology and Astronautics; Interior Architecture; Space Physics